Peran Chatgpt dalam Pembelajaran Menulis Bahasa Inggris Bagi Mahasiswa Ekonomi Syariah: Perspektif Mahasiswa di STIES Mitra Karya Bekasi - Noviarini, Tiara (Universitas Muhammadiyah Surabaya, 2025)
This study aims to describe the role of ChatGPT in English writing learning among Islamic Economics students at STIES Mitra Karya Bekasi based on their experiences and perceptions. A descriptive qualitative approach was employed with data collected through in-depth interviews, indirect observations, and documentation of students’ written works using ChatGPT. Data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The results indicate that ChatGPT plays a significant role in enhancing students’ writing skills, particularly in enriching vocabulary, improving sentence structure, and increasing motivation and self-confidence in writing. However, several challenges were identified, such as dependence on technology, reduced originality of writing, and decreased critical thinking ability. Therefore, ChatGPT should be positioned as a supportive learning tool rather than a substitute for students’ independent thinking and creativity in academic writing.